Determinants of functional specialisation in EU countries - Aleksandra Kordalska; Magdalena Olczyk (Hans-Böckler-Stiftung, 2023)
Functional specialisation in global value chains is a complex phenomenon. This paper examines the determinants of functional specialisation patterns in EU countries, focusing on the business functions fabrication and research and development. The core result of the study is that lower wages favour functional specialisation in fabrication activities, while higher wages promote specialisation in research and development activities. The result is robust with respect to using different methodologies for measuring functional specialisation.
Keywords: 330; global values chains trade; R&D; GVC; research and development